Manajemen Rekrutmen Dan Seleksi Di Era Digital - Dwiana Agustiningrum; Caryati Caryati; Dian Varietasari; Ngurah Ayu Nyoman Murniati (Educatio, 2026)
The development of digital technology has fundamentally transformed human resource management, particularly in employee recruitment and selection processes. Digitalization enables organizations to automate hiring procedures, expand candidate reach, and make data-driven decisions through technologies such as Artificial Intelligence (AI), Applicant Tracking Systems (ATS), and People Analytics. This study employs a literature review method to examine the transformation of recruitment and selection for educational personnel in the digital era, analyzing relevant theories, practices, and emerging ethical challenges. Findings indicate that digital recruitment enhances time and cost efficiency, increases objectivity in selection, and strengthens employer branding. However, it also presents new challenges, including algorithmic bias, data privacy concerns, and a digital skills gap among HR practitioners. Therefore, effective recruitment strategies should integrate technological innovation with human values, transparency, and professional ethics. The study recommends enhancing HR digital competencies, implementing algorithmic ethics audits, and developing recruitment systems that balance efficiency with fairness and social responsibility.